Ankle Mortise Fractures as a Cause of Functional Impairment: Current Concepts in Diagnosis, Treatment, and Rehabilitation: Current Concepts in Diagnosis, Treatment, and Rehabilitation - Fabiś, Katarzyna; Zbylut, Mateusz; Kossakowski, Daniel Filip; Byjoś, Ewa; Buczek, Sylwia; Mstowska, Weronika; Bury, Karolina; Naliuka, Hanna; Młynarczyk, Katarzyna; Mateja, Patrycja (Journal of Education, Health and Sport, 2026)
Background. Ankle mortise fractures represent a common injury of the lower extremity and are associated with a wide spectrum of instability and functional impairment. Due to the complex anatomy of the ankle joint and the critical role of the distal tibiofibular syndesmosis in maintaining joint congruency, these fractures may lead to prolonged disability, chronic pain, and post-traumatic osteoarthritis if not properly managed. Aim. To review current evidence regarding ankle mortise fractures, with particular emphasis on etiology, classification, diagnostic strategies, treatment options, rehabilitation protocols, and functional outcomes. Material and methods. A narrative review of the literature was conducted using PubMed, Scopus, and Google Scholar. Peer-reviewed articles published in English concerning adult patients with ankle mortise fractures were included. Original studies, systematic reviews, and clinical practice guidelines were analyzed qualitatively. Results. The literature indicates that ankle mortise fractures account for a significant proportion of ankle injuries and frequently result from rotational mechanisms. Accurate assessment of fracture stability and syndesmotic integrity is essential for treatment selection. Conservative management yields favorable outcomes in stable fracture patterns, whereas unstable injuries typically require surgical fixation. Early mobilization and structured rehabilitation improve functional recovery, while delayed or inadequate management increases the risk of long-term complications. Conclusion. Ankle mortise fractures are a clinically relevant cause of functional limitation and reduced mobility. Optimal outcomes depend on accurate diagnosis, appropriate treatment selection, and early, individualized rehabilitation. A comprehensive, evidence-based approach is essential to restore function and minimize long-term complications